Sexual Reproduction in Animals and Plants 2014
DOI: 10.1007/978-4-431-54589-7_22
|View full text |Cite
|
Sign up to set email alerts
|

Signaling Events in Pollen Acceptance or Rejection in the Arabidopsis Species

Abstract: The initial events of pollen-pistil interactions are fundamentally important in fl owering plants because they infl uence successful fertilization. These early events include the recognition of pollen grains through signaling events in the pistil that will lead to the acceptance of a compatible pollen grain or the rejection of an incompatible pollen grain. There has been much research into this fi eld in the Brassicaceae, as this family includes many agriculturally important crops such as canola, radish, turni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 96 publications
0
5
0
Order By: Relevance
“…In Arabidopsis, pollen-pistil interactions trigger a cascade of complex events in stigmatic papillae that mediate the acceptance of compatible pollen and the rejection of self-incompatible pollen (for review, see Indriolo et al, 2014b). While considerable progress has been made in deciphering the cellular signaling regulating the rejection of self-incompatible pollen in the Brassicaceae (for review, see Iwano and Takayama, 2012;Dresselhaus and Franklin-Tong, 2013;Indriolo et al, 2014b), comparatively little is known about the cellular responses of stigmatic papillae to compatible pollen.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In Arabidopsis, pollen-pistil interactions trigger a cascade of complex events in stigmatic papillae that mediate the acceptance of compatible pollen and the rejection of self-incompatible pollen (for review, see Indriolo et al, 2014b). While considerable progress has been made in deciphering the cellular signaling regulating the rejection of self-incompatible pollen in the Brassicaceae (for review, see Iwano and Takayama, 2012;Dresselhaus and Franklin-Tong, 2013;Indriolo et al, 2014b), comparatively little is known about the cellular responses of stigmatic papillae to compatible pollen.…”
Section: Discussionmentioning
confidence: 99%
“…While considerable progress has been made in deciphering the cellular signaling regulating the rejection of self-incompatible pollen in the Brassicaceae (for review, see Iwano and Takayama, 2012;Dresselhaus and Franklin-Tong, 2013;Indriolo et al, 2014b), comparatively little is known about the cellular responses of stigmatic papillae to compatible pollen. Previously, we have demonstrated that EXO70A1 is an essential factor in the stigma for compatible pollen-pistil interactions in Arabidopsis and B. napus promoting pollen hydration and pollen tube penetration into the stigma surface (Samuel et al, 2009;Safavian et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During the interactions between the pollen and stigma, a series of events occur in succession, including pollen adhesion onto the stigma, pollen hydration and germination, and the polarized growth of pollen tubes across stigmatic tissue. In recent years, the interactions between the pollen and stigma have been studied in a number of plant species [ 3 , 4 ]. However, determining the mechanisms underlying these interactions remains a major challenge.…”
Section: Introductionmentioning
confidence: 99%